2017
DOI: 10.1186/s12882-017-0507-8
|View full text |Cite
|
Sign up to set email alerts
|

Delta neutrophil index is an independent predictor of mortality in septic acute kidney injury patients treated with continuous renal replacement therapy

Abstract: BackgroundDelta neutrophil index (DNI), representing an elevated fraction of circulating immature granulocytes in acute infection, has been reported as a useful marker for predicting mortality in patients with sepsis. The aim of this study was to evaluate the prognostic value of DNI in predicting mortality in septic acute kidney injury (S-AKI) patients treated with continuous renal replacement therapy (CRRT).MethodThis is a retrospective analysis of consecutively CRRT treated patients. We enrolled 286 S-AKI pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In evaluating septic conditions, the DNI is therefore more valuable than the leucocyte count as it reflects the circulating immature granulocyte count irrespective of the leucocyte count 45 . Additionally, several studies have found that the DNI has the advantages of accuracy and rapidity in evaluating infection 22 , 23 , 39 . Hence, although the DNI is not widely used, these characteristics and advantages motivated us to evaluate further its value as a clinical prognostic biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…In evaluating septic conditions, the DNI is therefore more valuable than the leucocyte count as it reflects the circulating immature granulocyte count irrespective of the leucocyte count 45 . Additionally, several studies have found that the DNI has the advantages of accuracy and rapidity in evaluating infection 22 , 23 , 39 . Hence, although the DNI is not widely used, these characteristics and advantages motivated us to evaluate further its value as a clinical prognostic biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, DNI is a predictive marker of histological chorioamnionitis in patients with preterm premature rupture of membranes . A higher DNI is a prognostic marker of out‐of‐hospital cardiac arrest and an independent factor of mortality in septic acute kidney injury patients with continuous renal replacement therapy . Septic condition of patients who visited the emergency room is an important factor for predicting their prognosis and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…13 A higher DNI is a prognostic marker of out-of-hospital cardiac arrest 14 and an independent factor of mortality in septic acute kidney injury patients with continuous renal replacement therapy. 15 Septic condition of patients who visited the emergency room is an important factor for predicting their prognosis and mortality. Therefore, there have been efforts to find proper biomarkers associated with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study showing a relationship between PCO 2 and the outcomes of patients treated with CRRT. Previous studies related to the predictive factors for survival renal recovery of the critically ill patients receiving CRRT focused on status of fluid, serum creatinine, glomerular filtration rate [10, 14, 15], coagulation functions [7, 16], inflammatory related mediators [5], and electrolyte and mineral disturbances [6]. However, there were few studies investigating parameters from respiratory system predicting survival with CRRT therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Both patient status and CRRT modality will affect patient outcomes. Some of cohort tried to find out the relationship of CRRT-related variables and hospital mortality [2-4], and several patient-related biomarkers have been investigated to be associated with mortality of CRRT patients [5-10]. With the improvement of techniques and methods of CRRT, indications of CRRT were far more than renal dysfunction.…”
mentioning
confidence: 99%